Systematic Reanalysis of KMTNet Microlensing Events. II. Two New Planets in Giant-source Events - Hongjing Yang; Jennifer C. Yee; Jiyuan Zhang; Chung-Uk Lee; Dong-Jin Kim; Ian A. Bond; Andrzej Udalski; Kyu-Ha Hwang; Weicheng Zang; Qiyue Qian; Andrew Gould; Shude Mao; et al. (The Astronomical Journal)
In this work, we continue to apply the updated KMTNet tender-love care photometric pipeline to historical microlensing events. We apply the pipeline to a subsample of events from the KMTNet database, which we refer to as the giant source sample. Leveraging the improved photometric data, we conduct a systematic search for anomalies within this sample. The search successfully uncovers four new planet-like anomalies and recovers two previously known planetary signals. After detailed analysis, two of the newly discovered anomalies are confirmed as clear planets: KMT-2019-BLG-0578 and KMT-2021-BLG-0736. Their planet-to-host mass ratios are q  ∼ 4 × 10 ^−3 and q  ∼ 1 × 10 ^−4 , respectively. Another event, OGLE-2018-BLG-0421 (KMT-2018-BLG-0831), remains ambiguous. Both a stellar companion and a giant planet in the lens system could potentially explain the observed anomaly. The anomaly signal of the last event, MOA-2022-BLG-038 (KMT-2022-BLG-2342), is attributed to an extra source star. Within this sample, our procedure doubles the number of confirmed planets, demonstrating a significant enhancement in the survey sensitivity.